User Satisfaction Performance Analysis Of Midwives And Nurses Graduate Hospital In Semarang City And County - Sri Wahyuni; Wien Soelistyo Adi; Sudiyono Sudiyono (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Quality or the quality of graduates is very important so as to provide a positive impact on the change and the prospect of graduate nursing and midwifery in the future. The changes are expected to happen to nurses and midwives in the future is as a figure of professional nurses and midwives, to improve the quality of health service quality so as to give satisfaction to masyarakat.Tujuan research is Knowing user satisfaction on the performance of graduates of midwife-nurse at City Hospital and the District of Semarang. This study is correlational research with cross sectional approach. The research instrument used structured questionnaires Total sample 140 respondents (patients), and 70 assessments of the respondents (supervisor) on graduates (midwives and nurses) working in the department of Dr Kariadi Semarang, Semarang Tugurejo Public Hospital and the hospital district Ambarawa Semarang. the purposive sampling technique sampling with proportional allocation. Bivariate analysis using Pearson product moment test. The results show that the graduates have a long working period ( 5 years) that a number of 44 (62.9%), with a Diploma III education. There was a strong correlation between the perception of the user (and the patient's immediate supervisor) about the quality of health worker's satisfaction with the results of the p value 0.0001 persessi the higher the quality, the higher the satisfaction. Needs to be done coaching, motivation to midwives and nurses to improve the performance of health care based on competence good knowledge, attitudes and skills, so as to give satisfaction to the user.